Penerapan Administrasi Perdagangan secara Digital dalam Kegiatan Manajemen Perseroan Terbatas Gerbang NTB Emas - Chandra, Hendika; Ni Luh Darmasanti Aprilia Ulandari; Nelson Liem; Rini Anggriani (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
Digitalization, marked by advanced technology, has transformed human life, making it more practical. This transformation also impacts PT. Gerbang NTB Emas, which requires efficient transaction administration systems. Therefore, this service activity aims to help PT. Gerbang NTB Emas implement various digital financial recording systems. The method of implementing this activity includes recording, summarizing, and archiving general expenditures, cross-checking item prices on the Mahadesa website system, updating and adjusting prices in the TDC Mahadesa system, and evaluation stages. Core activities include utilizing Microsoft Excel for financial recording, developing the Mahadesa web-based system for trade transaction administration, and collaborating with local governments to enhance village-level businesses. This series of activities was completed within one month. The results are the successful implementation of digital financial recording and improved trade transaction administration, which help maintain the efficiency and reliability of PT. Gerbang NTB Emas's operations. Through this activity, it is hoped that the company can continue to enhance its digital financial and administrative practices, achieving a balance between practical and theoretical understanding for future growth.